Presenting Yourself : A Personal Image Guide for Women - Spillane, Mary (London Color Me Beautiful Orangination, 1993)
This sequel to "The Complete Style Guide from Color Me Beautiful" is aimed at the working woman. The book explains that how you are packaged and your image, shows how you value yourself and respect others and shows women how they can present themselves in the best possible light.
Include Color Illustrations, Bibliography and Index
Keywords: Success in business -- Businesswomen -- Clothing and dress